(untitled) (Altre Modernità, 2012)
This article explores the regressive pursuit of paradise Job makes upon the onset of his calamities – his numerous losses, followed by the onset of sore boils. A figure uncannily resembling the prelapsarian Adam, Job (also innocently naked) curses all creation. By the end of the book of Job, God manages to quell Job’s opposition through his speech out of the whirlwind. Yet what Job has done, and what the book of Job does, is alert readers of the problematic dimension of creation. Job’s insistence on returning to the void maddens God because God and the void were, prior to creation, one: the God-void, the void-God. Through the act of creation, though, God, in his pursuit of alterity, originates evil by denying his very being and banishing the void. When God “re-creates” creation before Job, one thus realizes God is actually attempting to convince the void of the goodness of creation and to reunite with the void – which, of course, the void will not do, for to do is to act, and to act would be to divide its being. Thus, Job’s summoning of the void (even if he conceives of it as an immaterial substance and not also a being, a former component of God) is not just for every created person’s sake, but also for God’s sake; by returning to the void, God would ultimately be undivided once more. Such, then, is the regressive paradise which emerges from the book of Job – a paradise which cannot be, but which Job (and perhaps even God) longs for nonetheless.